A crop for a forest: Opuntia ficus-indica as a tool for the restoration of Mediterranean forests in areas at desertification risk - Bueno, Rafael Silveira; Badalamenti, Emilio; Sala, Giovanna; La Mantia, Tommaso (Frontiers in Forests and Global Change, 2024)
Introduction The Mediterranean is the European region with the lowest woody cover and the highest level of habitat degradation, being highly susceptible to climate change effects and desertification risk. In such worrying conditions, increasing woody cover and restoring forests is a major goal established in several international commitments. However, recruitment limitation of woody species is rather frequent both within natural regeneration processes and active restoration programs, particularly due to drought, overgrazing, and a lack of post-planting tending operations. Therefore, finding suitable tools to improve the recruitment success of native woody species is of crucial importance. Methods We assessed woody natural regeneration under abandoned prickly pear orchards, olive trees, and nearby open areas in three sites under high desertification risk in central Sicily (Italy). Then, we tested for differences in density, richness, diversity, height, and basal diameter of the woody recruiting species between these three habitats. Results and discussion Natural regeneration was widespread under prickly pear, with 94.6% of the sampled plots showing at least one recruit, in comparison to 61.6% of plots under olive and 22.3% in open areas. Natural regeneration density under prickly pears (114 ± 99 individuals m−2) was significantly higher (p < 0.001) than under olive trees (60.4 ± 76.4) and open areas (4.6 ± 9.3). Recruits’ diversity, basal diameter, and height were also significantly higher under prickly pear, concentrating 94.4% of the individuals higher than 100 cm and all late successional species. Our results indicate a great potential for prickly pears to accelerate the natural regeneration of Mediterranean woody species in areas under desertification. However, a site-specific evaluation must be made taking into account prickly pear’s historical presence, temporary income as a crop, management capacity and, especially, its invasive potential.